Bringing it home: community survey of HIV risks to primary sex partners of men and women in alcohol-serving establishments in Cape Town, South Africa. - Kalichman, Seth C; Pitpitan, Eileen; Eaton, Lisa; Cain, Demetria; Carey, Kate B; Carey, Michael P; Harel, Ofer; Mehlomakhulu, Vuyelwa; Simbayi, Leickness Chisamu; Mwaba, Kelvin (Sexually transmitted infections, 2013)
Concurrent sexual relationships facilitate the spread of HIV infection, and sex with non-primary partners may pose particularly high risks for HIV transmission to primary partners.